An enquiry based on a standardised questionnaire into knowledge, awareness and preferences concerning the care of familial hypercholesterolaemia among primary care physicians in the Asia-Pacific region: the "Ten Countries Study". Issue 10 (25th October 2017) - Pang, Jing; Hu, Miao; Lin, Jie; Miida, Takashi; Nawawi, Hapizah M; Park, Jeong Euy; Wu, Xue; Ramli, Anis S; Kim, Ngoc Thanh; Kwok, See; Gonzalez-Santos, Lourdes E; Su, Ta-Chen; et al.
Abstract : Objective: To determine physicians' knowledge, awareness and preferences regarding the care of familial hypercholesterolaemia (FH) in the Asia-Pacific region. Setting: A formal questionnaire was anonymously completed by physicians from different countries/regions in the Asia-Pacific. The survey sought responses relating to general familiarity, awareness of management guidelines, identification (clinical characteristics and lipid profile), prevalence and inheritance, extent of elevation in risk of cardiovascular disease (CVD) and practice on screening and treatment. Participants: Practising community physicians from Australia, Japan, Malaysia, South Korea, Philippines, Hong Kong, China, Vietnam and Taiwan were recruited to complete the questionnaire, with the UK as the international benchmark. Primary outcome: An assessment and comparison of the knowledge, awareness and preferences of FH among physicians in 10 different countries/regions. Results: 1078 physicians completed the questionnaire from the Asia-Pacific region; only 34% considered themselves to be familiar with FH. 72% correctly described FH and 65% identified the typical lipid profile, with a higher proportion of physicians from Japan and China selecting the correct FH definition and lipid profile compared with those from Vietnam and Philippines. However, less than half of the physician were aware of national or international management guidelines; this was significantly worse than physicians from the UK (35% vs 61%, p<0.001). Knowledge of prevalence (24%), inheritability (41%) and CVD risk (9%) of FH were also suboptimal. The majority of the physicians considered laboratory interpretative commenting as being useful (81%) and statin therapy as an appropriate cholesterol-lowering therapy (89%) for FH management. Conclusions: The study identified important gaps, which are readily addressable, in the awareness and knowledge of FH among physicians in the region. Implementation of country-specific guidelines and extensive work in FH education and awareness programmes are imperative to improve the care of FH in the region.